Effects of shadowing on LoRa LPWAN links - Chowdhury, Israth Jahan (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
LoRaWAN is a long-range, low-power, wireless telecommunications system that is expected to play a large role for the Internet of Things. End appliances use LoRaWAN through a sole wireless hop to communicate with gateways (sinks) which are connected to the Internet that function as see-through bridge relaying messages amongst these end-appliances and as a core network server. This eliminates the requirement of assembling and maintaining a complex multihop network. A variety of communication alternatives (e.g. carrier frequency, spreading factor, bandwidth and coding rates) are also provided by LoRa as of which a transmitter can select. The technology offers a very compelling mix of long range, low power consumption and secure data transmission and is gaining wide acceptance in IoT network operators worldwide. The operation of LoRa network server is made ﬂexible and scalable by making use of the system services offered. However, no comprehensive evaluation of the technology exists in the open literature. The key intention of this research study is to investigate the effects of shadowing on LoRaWAN links and analyze the performance in terms of the capacity, coverage, scalability and outage probability for different physical layer settings in order to achieve more optimized operation of LoRa network. This was done by means of simulation modelling. Results indicate large differences in performance when shadowing is taken into consideration upsetting the expected performance tremendously from what is being touted in the literature. For example, on long links of 4km-15km, the number of lost packets can reach up to 100% even though the number of sinks is increased in the network. Furthermore, the throughput shows ups and downs from 0% to 100 % while no shadowing is included.